Experimental observations and modelling of intrinsic rotation reversals in tokamaks. (23rd January 2017) - Camenen, Y; Angioni, C; Bortolon, A; Duval, B P; Fable, E; Hornsby, W A; McDermott, R M; Na, D H; Na, Y-S; Peeters, A G; Rice, J E
Abstract: The progress made in understanding spontaneous toroidal rotation reversals in tokamaks is reviewed and current ideas to solve this ten-year-old puzzle are explored. The paper includes a summarial synthesis of the experimental observations in AUG, C-Mod, KSTAR, MAST and TCV tokamaks, reasons why turbulent momentum transport is thought to be responsible for the reversals, a review of the theory of turbulent momentum transport and suggestions for future investigations.